Shanghai’s Regenerated Industrial Waterfronts: Urban Lab for Sustainability Transitions? - den Hartog, Harry (2021)
In China, Shanghai often serves as a place to introduce and try out new ideas. This is certainly the case with experimental urban planning and design solutions and sustainability transitions. This article identifies and evaluates the role of pilot projects and demonstration zones along the Huangpu River. These clusters and zones are supposed to guide the urban regeneration of the former industrial waterfronts and to accelerate innovative development in Shanghai and the wider Yangtze Delta Region. The Huangpu River as a whole is considered an urban lab and a showcase of ecological civilisation policies, with a strong ‘people oriented’ focus on improving the overall quality and attractiveness of urban life. Following three decades of rapid urban expansion, Shanghai’s urban development model is shifting toward one that emphasizes densification and the reuse of existing elements. The motto of Shanghai’s latest master plan is “Striving for an Excellent Global City.” One of the pathways to realize this expectation is the creation of thematic clusters for creative industries, financial institutes, AI, and technology, media and telecommunication industries. These clusters are high-density investment projects meant to support and accelerate the transformation of Shanghai into a service economy. There are important similarities between these projects in Shanghai and the role of urban labs in theories of sustainability transitions. Drawing on these theories and those of ecological civilization, this article examines how these so-called ‘experimental’ urban megaprojects along the river contribute to Shanghai’s effort to take the lead in developing sustainable urban transitions.